A MATHEMATICAL MODELING WITH OPTIMAL CONTROL STRATEGY OF TRANSMISSION OF COVID-19 PANDEMIC VIRUS. (2020) - KOUIDERE, ABDELFATAH; KHAJJI, BOUCHAIB; BHIH, AMINE EL; BALATIF, OMAR; RACHIK, MOSTAFA
No abstract available